Below the line - Gould, Howard Michael (A Charlie Waldo novel, 2019)
Former LAPD detective Charlie Waldo was living in solitude deep in the woods, pathologically committed to owning no more than one hundred possessions, until his PI ex-girlfriend Lorena dragged him back to civilization to solve a high-profile Hollywood murder. Now Waldo and Lorena have their hands full with a new client, a wild and privileged L.A. teenager named Stevie Rose who tells lies as easily as she breathes. When the teacher Stevie claims seduced her turns up dead, the LAPD pegs her as the prime suspect. Then Stevie disappears, and her self-involved Hollywood parents turn to Waldo to find her<U+2014>a task that draws him down into Orange County<U+2019>s dangerous and complex worlds, both opulent and seedy, where nothing is as it seems. With treachery and deception at every turn, and with Waldo<U+2019>s eco-obsessed rules for living complicating his already complicated relationship with Lorena, Waldo fends off enemies old and new as he races to find Stevie and solve the murder.